Reflections on the past, present, and potential futures of knowledge hierarchies in ocean biodiversity governance research - Holly J. Niner; David Wilson; Kelly Hoareau; Mia Strand; Jennifer Whittingham; Dylan McGarry; Bolanle Erinosho; Sulley Ibrahim; Sirkka Tshiningayamwe; Senia Febrica; Alana Malinde S. N. Lancaster; Milica Prokic (Frontiers in Marine Science, 2024)
Governance of the ocean and its biodiversity is deeply entangled within social, political and cultural histories. The evolution of marine science has been subject to similar influences, and we (the authors) consider these factors to create, embed and reinforce knowledge hierarchies in ocean governance processes and associated research that set societal patterns of prioritisation and exclusion. Such knowledge hierarchies have constructed dominant Western-oriented knowledge systems as ‘rational’ and ‘objective’ approaches to environmental governance in contrast to non-Western knowledge systems and have led to a dominance of natural (normal) sciences over centralised biodiversity governance. The extraction and incorporation of traditional knowledge into the Western-oriented scientific canon through myriad historical and contemporary processes in ocean biodiversity governance often reproduce knowledge hierarchies, do not benefit knowledge holders and are often considered incomplete, inappropriate or absent. As we address current ocean biodiversity and conservation challenges, researchers must be aware of the history of knowledge extraction, impositions and assumptions within their fields. Researchers must also actively acknowledge and address these histories in their work to avoid marginalisation and support ethical, empathetic, and rigorous knowledge production that meets the needs of society. In this paper, through a development of the concept of knowledge hierarchies, we explore case studies of research diverse in geography and discipline ranging from action research in Namibia, the application of arts-based methodologies in legal proceedings to research focused at an international level, and the concept of ocean literacies, all of which are located under the umbrella of a project specifically targeting transformative ocean governance. It becomes evident that knowledge hierarchies are multi-layered, perpetuating, and often reproduced even when attempting to address hierarchies through such methods as the integration or ‘bringing together’ of diverse knowledge systems. Effective change will therefore require sensitive and multi-faceted approaches to knowledge hierarchies, including processes of embracing discomfort, which will be important to work with, as well as through. While there will be continued tensions between hierarchies, it is a sine qua non that researchers need to build a commitment to understanding where powers lie, rather than ignoring such imbalances or, similarly, by idealising approaches.